Enhancing the brightness of CsPbBr3 quantum dot electroluminescence light-emitting diodes by manipulation of PEDOT:PSS films. Issue 44 (2nd November 2021) - Wang, Zhen; Peng, Yue; Lu, Yongsheng; Tang, Xiaosheng; Tan, Xing; Liang, Zhenshan; Huang, Qiang; Qi, Fei; Zhang, Nan; Chen, Weiwei
Abstract : This work outlines the manipulation of the hole transport layer PEDOT:PSS films of QLED devices by three methods, air annealing, toluene vapor annealing, and EG washing to improve device performance. Abstract : With solution-processability, low-temperature proper energy level and superior stability, poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is one common hole-transport material for the quantum dot light-emitting diode (QLED) application. However, the conductivity of the traditional PEDOT:PSS is very low, which has an adverse effect on QLED devices. Herein, one surface-annealing method for the PEDOT:PSS film to exchange their original composition and surface morphology is proposed. The advantage of this approach lies in the fact that the conductivity of the PEDOT:PSS film annealed with toluene (1.25 S cm −1 ) and ethylene glycol (EG, 10.52 S cm −1 ) are obviously improved compared with the air-annealing method (0.13 S cm −1 ). The difference is that the EG-washed PEDOT:PSS film shows a relatively rough surface with more PEDOT domains, whereas the toluene treated PEDOT:PSS film can promote the formation of a smooth, PSS-dominated surface and change the PEDOT chain structure from coiled to linear, thus, the conductivity of the PEDOT:PSS film is enhanced. As a result, the QLED device achieves a maximum luminance of 31 140 cd m −2 and power efficiency of 13.4 lm W −1, showing 48% and 25% enhancements, respectively, compared to the control device. This work provides an efficient approach for improving of perovskite QLED performance.